Continuous resin tapping for frankincense harvest increases susceptibility of Boswellia papyrifera (Del.) Hochst trees to longhorn beetle damage. Issue 2 (February 2021) - Negussie, Aklilu; Gebrehiwot, Kindeya; Yohannes, Mekonnen; Norgrove, Lindsey; Aynekulu, Ermias
Abstract: Frankincense is an important tree resin that provides a livelihood in the semi-arid lower highlands of East Africa. In the absence of sustainable management strategies, Boswellia papyrifera trees were being overexploited, leading to a depletion of genetic diversity, affected by pests and diseases, failure in natural regeneration, and hence a subsequent decline in socio-ecological benefits obtained from the species. We studied the impact of (i) continuous resin tapping without resting years and (ii) tapping or wonding intensity for frankincence production on the prevalence of longhorn beetle ( Idactus spinipennis Gahan, Cerambycidae (sub family Lamiinae) damage in northern Ethiopia. We found that continuous resin tapping for frankincense harvest without adequate resting period made trees more vulnerable to longhorn beetle damage ( P < 0.05). Trees rested for 10 and more years from resin tapping had less beetle damage occurrence than those tapped continuously ( P < 0.05). Stem tapping intensity of more than 12 wounds per tree in one frankincense harvesting season caused high longhorn beetle damage incidence in Central Tigray (up to 90%) and Western Tigray (up to 80%). We recommend that B. papyrifera trees should have a resting period of at least 3 years and more after one year of continuous tapping. Depending on the size of a tree, wounding for frankincense harvest should be restricted to less than 12 wounds per tree. These measures would help the species develop resistance to longhorn beetle attack and maintain a healthy population for sustainable provision of ecosystem services including frankincense production in the dryalnds of northern Ethiopia. Abstract : Dryland; Habitat fragmentation; Idactus spinipennis ; Cerambycidae; Frankincense; Dry woodland, Ethiopia